Weak Iron Oxidation by Sulfobacillus thermosulfidooxidans Maintains a Favorable Redox Potential for Chalcopyrite Bioleaching - Christel, Stephan; Herold, Malte; Bellenberg, Sören; Buetti-Dinh, Antoine; El Hajjami, Mohamed; Pivkin, Igor V.; Sand, Wolfgang; Wilmes, Paul; Poetsch, Ansgar; Vera, Mario; Dopson, Mark (Frontiers in Microbiology, 2018)
Bioleaching is an emerging technology, describing the microbially assisted dissolution of sulfidic ores that provides a more environmentally friendly alternative to many traditional metal extraction methods, such as roasting or smelting. Industrial interest increases steadily and today, circa 15-20% of the world’s copper production can be traced back to this method. However, bioleaching of the world’s most abundant copper mineral chalcopyrite suffers from low dissolution rates, often attributed to passivating layers, which need to be overcome to use this technology to its full potential. To prevent these passivating layers from forming, leaching needs to occur at a low oxidation/reduction potential (ORP), but chemical redox control in bioleaching heaps is difficult and costly. As an alternative, selected weak iron-oxidizers could be employed that are incapable of scavenging exceedingly low concentrations of iron and therefore, raise the ORP just above the onset of bioleaching, but not high enough to allow for the occurrence of passivation. In this study, we report that microbial iron oxidation by Sulfobacillus thermosulfidooxidans meets these specifications. Chalcopyrite concentrate bioleaching experiments with S. thermosulfidooxidans as the sole iron oxidizer exhibited significantly lower redox potentials and higher release of copper compared to communities containing the strong iron oxidizer Leptospirillum ferriphilum. Transcriptomic response to single and co-culture of these two iron oxidizers was studied and revealed a greatly decreased number of mRNA transcripts ascribed to iron oxidation in S. thermosulfidooxidans when cultured in the presence of L. ferriphilum. This allowed for the identification of genes potentially responsible for S. thermosulfidooxidans’ weaker iron oxidation to be studied in the future, as well as underlined the need for mechanisms to control the microbial population in bioleaching heaps.